If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 2) + 4x = x + 6 Reorder the terms: 2(2 + x) + 4x = x + 6 (2 * 2 + x * 2) + 4x = x + 6 (4 + 2x) + 4x = x + 6 Combine like terms: 2x + 4x = 6x 4 + 6x = x + 6 Reorder the terms: 4 + 6x = 6 + x Solving 4 + 6x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + 6x + -1x = 6 + x + -1x Combine like terms: 6x + -1x = 5x 4 + 5x = 6 + x + -1x Combine like terms: x + -1x = 0 4 + 5x = 6 + 0 4 + 5x = 6 Add '-4' to each side of the equation. 4 + -4 + 5x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 6 + -4 5x = 6 + -4 Combine like terms: 6 + -4 = 2 5x = 2 Divide each side by '5'. x = 0.4 Simplifying x = 0.4
| 9+c=-13 | | 4(s+2)-s=3(s+1) | | t=4n+4v | | 0.3(y+1)-0.4(3-2y)=0.2 | | 7x+5-4x-4=x | | (5cd^2)(-c^4d)= | | n^2+n+132=0 | | 2.5x+2.1=5.3 | | 5z^2-35=0 | | -4x^2+3x+10=0 | | 3u+45=9u+81 | | 3x-5=3(x+9) | | -3(x+1)+4x=13 | | 6y-6=48 | | 0.375n-2=0.25n | | 4x+5y=11 | | 1.2x+8=-2 | | 18x-13=7(2x-1)+4x-6 | | 2y+4x=2 | | y=4*x^2 | | 3X^2+10X=2000 | | 2x-x+48=12x+48 | | 12(3p)-3p=33P+12 | | (2y+3)(2y+3)=9 | | 4+7x=2-(1+x) | | 0.25y-0.15y+3=4 | | 45a+6=7a | | u^2-7u=8 | | -7+5+(-10)+7= | | 4.9(4+4x)-5.6=14 | | 6(9)-6=x | | 45=0.5h(10+5) |